2017
DOI: 10.1002/ijc.30610
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and risk of endometrial cancer in the Norwegian Women and Cancer (NOWAC) study

Abstract: Few studies have investigated the association between endometrial cancer and physical activity (PA) using repeated measures of PA and different subtypes of endometrial cancer. We aimed to investigate the association between endometrial cancer and PA level at two points in time in women with different body mass index (BMI) profiles, and to calculate the population attributable fraction (PAF) of endometrial cancer for low PA levels. We included 82,759 women with complete information on PA at baseline in the Norw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 41 publications
1
19
1
3
Order By: Relevance
“…(6) Two cohort studies identified in the updated search found statistically significant associations between high versus low levels of physical activity and reduced risk of endometrial cancer. (26,27) Esophageal Cancer: The PAGAC identified three meta-analyses/systematic reviews and one pooled analysis on physical activity and esophageal cancer risk. The most comprehensive was a 2014 meta-analysis(28) that included 24 individual studies of which 9 were cohort and 15 were case-control studies.…”
Section: Cancer Primary Preventionmentioning
confidence: 99%
“…(6) Two cohort studies identified in the updated search found statistically significant associations between high versus low levels of physical activity and reduced risk of endometrial cancer. (26,27) Esophageal Cancer: The PAGAC identified three meta-analyses/systematic reviews and one pooled analysis on physical activity and esophageal cancer risk. The most comprehensive was a 2014 meta-analysis(28) that included 24 individual studies of which 9 were cohort and 15 were case-control studies.…”
Section: Cancer Primary Preventionmentioning
confidence: 99%
“…Our chained imputation models included all variables for the final Cox proportional hazards regression models and additional variables in order to predict incomplete variables or to predict whether the incomplete variable was missing [57]. This method has been developed and proved robust in several of studies within the NOWAC study [31][32][33]58], and the consistency with the complete-case analysis strengthens the results. Nevertheless, we cannot rule out that some of the information is still missing-not-at-random which may lead to biased estimations.…”
Section: Discussionmentioning
confidence: 90%
“…The pattern of missing was confirmed arbitrary. We used a similar imputation process as described in previous publications [31][32][33]. To reduce sampling variability, we created 20 replicate datasets from the imputation simulation [34].…”
Section: Multiple Imputationmentioning
confidence: 99%
“…13,14,25,26 The second sensitivity analysis grouped all tumors with morphology code 8140 (EC-not other specified [NOS]) as type 1 EC, except all grade 3+ tumours that were classified as type 2 EC. 10,25,26 By assuming a causal relationship between exposure and outcome as well as independence between risk factors, it is possible to estimate the population attributable fraction (PAF) in a national representative cohort like the NOWAC study. PAF describes the preventable proportion of the disease incidence related to the exposure over a certain time-period.…”
Section: Discussionmentioning
confidence: 99%